Let's solve the equation \( 2x - 5 = 3(4x + 5) \) following the provided steps.
Step 1: Distributive Property
First, we need to apply the distributive property on the right side of the equation:
\[ 3(4x + 5) = 3 \cdot 4x + 3 \cdot 5 = 12x + 15 \]
Now, we can rewrite the equation as:
\[ 2x - 5 = 12x + 15 \]
Step 2: Move Variables to One Side of the Equation
Next, we will move the variable terms to one side. We can subtract \(12x\) from both sides of the equation:
\[ 2x - 12x - 5 = 15 \]
Combine like terms:
\[ -10x - 5 = 15 \]
Step 3: Move Constant to the Other Side of the Equation
Now, we want to move the constant term (-5) to the other side. To do this, we add 5 to both sides of the equation:
\[ -10x - 5 + 5 = 15 + 5 \]
This simplifies to:
\[ -10x = 20 \]
Step 4: Isolate Your Variable
Finally, we will isolate the variable \(x\). To do this, we divide both sides by -10:
\[ x = \frac{20}{-10} \]
This simplifies to:
\[ x = -2 \]
Final Solution
The solution to the equation \( 2x - 5 = 3(4x + 5) \) is:
\[ \boxed{-2} \]